Wages As The Most Effective Mechanism of Activation of The Human Factor - Kożak-Siara, Tatiana; Shurpenkova, Ruslana; Sarakhman, Oksana (Współczesne Problemy Zarządzania, 2022)
The article summarizes the evolution of theoretical views on the essence of wages as a socio-economic category. The dynamics of changes in the size of wages, subsistence level in Ukraine by social and demographic groups is studied. It is noted that wages are the most effective mechanism for activating the human factor and the use of labor potential. For this mechanism it is necessary to explore the existing qualification and creative potential of each employee, and ultimately, remuneration should depend entirely on the scientific validity and choice of methods of communication of wages from qualifications, determining the content of work performed, results and conditions in which it accumulates.